2010
DOI: 10.1143/jpsj.79.084706
|View full text |Cite
|
Sign up to set email alerts
|

Signature of a Z2 Vortex in the Dynamical Correlations of the Triangular-Lattice Heisenberg Antiferromagnet

Abstract: Dynamical properties of the classical Heisenberg antiferromagnet on the triangular lattice are investigated by means of a spin-dynamics simulation and an analytical calculation. While the model was suggested to exhibit a topological transition driven by the Z2-vortex bindingunbinding, weakness of the associated thermodynamic singularity has made it difficult to observe the evidence of the Z2 vortex experimentally so far, only some indirect support. Here, we show that the signature of the Z2-vortex excitation a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
30
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 32 publications
(47 reference statements)
4
30
1
Order By: Relevance
“…Because the Z 2 -vortex predicted in 2D TLHAs is a vortex of the chirality vectors defined by local 120 • structures, it results in essentially the same behavior as the trimer model when the correlation length is short. Recently, a theoretical study showed that the excitations of the Z 2 -vortex should produce diffuse scattering connecting the K points [9]. Interestingly, the previously predicted Q pattern of the diffuse scattering looks very similar to those in Figs.…”
supporting
confidence: 76%
See 3 more Smart Citations
“…Because the Z 2 -vortex predicted in 2D TLHAs is a vortex of the chirality vectors defined by local 120 • structures, it results in essentially the same behavior as the trimer model when the correlation length is short. Recently, a theoretical study showed that the excitations of the Z 2 -vortex should produce diffuse scattering connecting the K points [9]. Interestingly, the previously predicted Q pattern of the diffuse scattering looks very similar to those in Figs.…”
supporting
confidence: 76%
“…1(h) and 1(i). Furthermore, the Z 2 -vortex shows a crossover to the spin wave correlations as T decreases [9]. A recent electron spin resonance spectroscopy study of ACrO 2 further suggested the existence of the Z 2 -vortices at T > T N [36].…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…It has been suggested 8 that this finite-T feature in fact reflects a nontrivial phase transition associated with binding of Z 2 vortices permitted by the SO(3) structure. At present, our study, which aims to understand the global features of the deformed Heisenberg model at finite T and h, has nothing to add to this interesting issue, [34][35][36][37][38][39] the resolution of which requires more extensive Monte Carlo simulations.…”
Section: Influence Of Thermal Fluctuationsmentioning
confidence: 99%